Description of Leucocyte Differential Count in Pregnant Women with COVID-19 - Nabila Alifiah; Siemona L. E. Berhimpon; Glady I. Rambert (Medical Scope Journal, 2022)
Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a high rate of transmission. Pregnant women are at high risk of infection due to the changes in their physiological and immune systems. This study aimed to determine the leukocyte differential count leukocyte in pregnant women with COVID-19. This was a descriptive study with a retrospective approach, using secondary data of the patients’ medical records during the periode of July-August 2021 at Prof. Dr. R. D. Kandou Hospital, Manado. The results showed that of 57 pregnant women with COVID-19, 92% had normal leukocyte differential count, 100% had normal basophil and eosinophil counts, 12% had neutrophilia, 23% had lymphopenia, and 95% had normal monocyte counts. In conclusion, in pregnant women with COVID-19 at Prof. Dr. R. D. Kandou Hospital, the most common abnormalities in leucocyte differential count are lymphopenia and neutrophiliaKeywords: pregnant women; COVID-19; leukocyte differential count Abstrak: Coronavirus disease 2019 (COVID-19) yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mempunyai tingkat penularan yang sangat tinggi. Wanita hamil berisiko tinggi terinfeksi COVID-19 karena adanya perubahan fisiologik dan sistem imun. Penelitian ini bertujuan untuk mengetahui gambaran hitung jenis leukosit pada wanita hamil dengan COVID-19. Jenis penelitian yang digunakan ialah deskriptif retrospektif dengan menggunakan data sekunder rekam medik periode Juli-Agustus 2021 di RSUP Prof. Dr. R. D. Kandou. Hasil penelitian memperlihatkan bahwa dari 57 wanita hamil terkonfirmasi COVID-19, terdapat 92% dengan nilai hitung leukosit normal, 12% mengalami neutrofilia, 23% mengalami limfopenia, 95% memiliki nilai hitung monosit normal, dan 100% memiliki nilai hitung basofil dan eosinofil normal. Simpulan penelitian ini ialah kelainan hitung jenis leukosit yang paling sering ditemukan pada wanita hamil terkonfirmasi COVID-19 di RSUP Prof. Dr. R. D. Kandou ialah neutrofilia dan limfopenia.Kata kunci: wanita hamil; COVID-19; hitung jenis leukosit